Nursing students' motivational and self‐regulated learning during the COVID‐19 pandemic: A cross‐sectional study. (13th July 2022) - Cho, Sunhee; Jang, Sun Joo
Abstract: On‐site clinical training, which has been greatly hindered during the COVID‐19 pandemic, is essential in nursing practicum. This study aimed to identify the predictors of nursing students' motivational and self‐regulated learning in clinical nursing practicum during the pandemic. This cross‐sectional study aimed to identify the predictors of motivational and self‐regulated learning among nursing students in clinical nursing practicum during the COVID‐19 pandemic. An online survey was completed by 195 nursing students in Korea in 2021. Students' moral sensitivity and motivational and self‐regulated learning were assessed using the Moral Sensitivity Questionnaire and the Motivated Strategies for Learning Questionnaire. Multiple regression analysis revealed that moral sensitivity was the most potent predictor of motivational and self‐regulated learning, followed by online clinical practicum experience, determination to become a nurse, and online practicum type; these factors explained 21.0% of the variance. Practicum courses using a tailored hybrid model, combining online and in‐person approaches for imparting nursing practices and inspiring moral sensitivity, can enhance nursing students' motivational and self‐regulated learning. Modules to enhance nursing students' moral sensitivity should be included in online practicum curricula.